5-Aminolevulinic Acid Phosphate as an Immune System Enhancer Along with Vaccination Against SARS-CoV-2 Virus Infection: An Open-Label, Randomized Pilot Study - Norbert Berenzen; Riyadh Rehani; Andrea Ebeling; Marcus Stocker; Motowo Nakajima (Life, 2025)
Previous studies have shown that 5-aminolevulinic acid phosphate together with sodium ferrous citrate, which is marketed as a food supplement, appears to be an important metabolic regulator in depleted T cell metabolism. Therefore, it was hypothesized that its administration in subjects vaccinated against COVID-19 could enhance their immune system. Therefore, the aim of our proof-of-concept study was to determine the safety (by adverse events monitoring) and the tolerability (by subject questionnaires) and to investigate immune-boosting properties (by Immunoglobulins) in which 200 subjects were randomized in a ratio of 1:1 within 2 arms. In the intervention arm, the study product was administered together with the vaccines Covishield or Covaxin, and up to 21 days thereafter with a 150 mg daily dose, whereas in the control arm, the subjects were vaccinated only. No safety issues were detected, and the evaluation of the subject questionnaires showed no limitation of the well-being, which confirms the excellent tolerability of 5-aminolevulinic acid phosphate with sodium ferrous citrate. Moreover, the ‘Change in Immunoglobulin G levels’, although statistically insignificant, showed strong signals of its immune supportive potential. However, further studies are recommended to verify the results.